Study of antibacterial activities of the extracts of Neem, Pomegranate, and Tulsi and essential oils against Salmonella Typhi - Binte Ehsan, Tazreen (Brac University, 2023)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Microbiology, 2022.